The Influence of Budget Preparation Participation and Locus of Control on Health Center Managerial Performance - Rahman, Nur Adifa; Amirullah, Sufyan; Indayani; Asnidar; Nuraeni M (Universitas Sulawesi Barat, 2025)
This research endeavors to analyze the impact of Budget Preparation Participation and Locus of Control on the managerial performance of Health Centers in Mamuju Regency, employing SPSS as the analytical tool. The study population consisted of two Health Centers located in Mamuju Regency, with a total of 35 respondents selected via a saturated sampling technique. Primary data were gathered through the distribution of questionnaires. Multiple linear regression analysis was utilized to evaluate the data. The results indicate that Budget Preparation Participation positively affects the managerial performance of Health Centers. Additionally, Locus of Control is found to have a positive influence on managerial performance. When examined concurrently, both Budget Preparation Participation and Locus of Control significantly and positively affect Health Center managerial performance. It is recommended that future studies build upon these findings by incorporating moderating or intervening variables to further enhance understanding